Infant and Child Mortality Status of Bangladesh: A Study on Demographic and Health Survey (Asian Journal of Social Science Studies, 2018)
The objective of the study is to review in order to gain a better understanding of current status and achievement of child health and infant mortality related MDG‟s status from 2000 to 2014 in Bangladesh. In this regard, the study intends to review and analyze the MDG achievements status of Bangladesh mainly published by UNDP and BDHS. Building on the United Nations (UN) global conference of the 1990s, the United Nations Millennium Declaration 2000 marked a strong commitment which was adopted by 147 Heads of states, were what have become known as the eight Millennium Development Goals (UNDP, 2014). The overall proportion of birth attended by skilled health personnel increased by more than eight folds in the last two decades, from 5.0% in 1991 to 43.5% in 2012-2013 (MDG Report 2014). In this circumstance, the committed target for Bangladesh is to reduce to 143 by 2015. On the contrary, many national and international reports projected that in case of under-five year mortality, Bangladesh can be able to reach at 54 deaths per thousand live-births while the target is to reduce to 48 by 2015. Bangladesh has made considerable progress in child survival rate as the mortality has declined rapidly over the last 10-12 years. The successful programs for immunization, control of diarrheal disease and vitamin-A supplementation are considered to be the most significant contributors to the decline in child and infant deaths. MDG report 2014 says that despite these progresses, there still remain challenges. While the mortality rates have declined substantially, inequalities in terms of access and utilization of health services among the populations still need to be addressed. To improve the MDG-5, some aspects such as unhealthy environment‟s impact on childhood diseases, poor uses of maternal healthcare services, different types of injury risks, high malnutrition and various technical, non-technical and administrative loopholes can be under highly considered. Greater efforts are particularly required in populous countries with mortality. In addition to medical and nutritional factors, improvement in other areas- notably education, access to safe water and adequate sanitation, adequate food, child protection and women‟s empowerment will also improve prospects for child survival and development. This paper also suggests that achievement in child mortality is positive but accomplishment of immunization is very much demanding. In conclusion, the health related MDGs are closely interrelated and require a joint and comprehensive approach. Although some progress has been made, it is uneven and there are much more remains to be done.